Pengaruh Strategi Guru Terhadap Minat Belajar Siswa Kelas IX dalam Pembelajaran PAI di MTs Annurain Lonrae - Nurdadia, Nurdadia (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This thesis discusses about the influence of teacher strategy in learning PAI toward the interest of student of the 9th grade in MTs. Annurain Lonrae and has purpose of this research to analyze the influence of teacher strategy on students learning interest of 9th grade in PAI learning at MTs. Annurain Lonrae. This research is field research by using mixed method. It uses pedagogical, psychological and sociological approach. The population is all 9th grade students in MTs. Annurain Lonrae. Data are collected by observation method, questioners, interview, documentation, and reference searching. The data processing technique is done by summing the score and making the table of teacher strategy in PAI learning and students interest in MTs. Annurain Lonrae, and then the data is processed and analyzed by using simple linear regression test through statistical product and service solution (SPSS) version 18. The results showed that student center learning strategy has been implemented well by teachers in learning, although not yet optimal. Students learning interest focused on the learning process of PAI has started to look better than before. Proven with the acquisition of questionnaires that have been processed and analyzed by researchers using SPSS showed that the score of t equal to 5831 with the value of significant (Sig. score 0.05) then it can be concluded H0 rejected and H1 accepted, it means there is a significant effect of student centered strategy to students learning interest in learning PAI in MTs Annurain Lonrae.